What kind of crop insurance for Russia? - Andreas Wildermuth (Institute of Agricultural Development in Central and Eastern Europe (IAMO), 1999)
The paper starts with an analysis of the decline of Russian state-subsidised all-risk crop insurance during the transition period, describes the reorganisation of Russian crop insurance started in 1997 and 1998, and compares the Russian experience with the Czech Republic's strictly commercial approach to crop insurance reform. A discussion of the pros and cons of multiple-peril/all-risk crop insurance yields the result that there is no allocative justification for subsidised all-risk and multipleperil crop insurance. The subsequent discussion of alternative approaches to the design of crop insurance vindicates the Czech approach in so far as coverage is restricted to a limited number of perils. But this does not necessarily mean that the government should in all circumstances abstain from intervention in crop insurance markets. Under certain conditions compulsory insurance and subsidies can contribute to an increase in social welfare. The conclusion for Russia is that the present subsidised all-risk crop insurance scheme should be abolished and replaced with specific-risk crop insurance which offers coverage for a limited number of perils. A potential example would be insurance against the risk of yield losses by the hot and dry steppe wind sukhovei. The if and how of government intervention in crop insurance should be decided pragmatically, depending on the circumstances of the peril under consideration. – – Das Papier beginnt mit der Analyse des Niedergangs der russischen staatlich subventionierten AllGefahren-Ertragsausfallversicherung in der Transformationsperiode, stellt die in den Jahren 1997 und 1998 angelaufene Reorganisation der russischen Ernteversicherung dar und vergleicht die Erfahrungen in Rußland mit dem strikt kommerziellen Ansatz der Tschechischen Republik zur Reform der Ertragsausfallversicherung. Eine Diskussion des Für und Wider von Vielgefahren/ Allgefahren-Ertragsausfallversicherungen führt zu dem Ergebnis, daß es keine allokative Rechtfertigung für die subventionierte Allgefahren/Vielgefahren-Ertragsausfallversicherung gibt. Im Anschluß werden alternative Formen der Ausgestaltung von Agrarversicherungssystemen diskutiert. Diese Analyse bestätigt die Richtigkeit des tschechischen Ansatzes insoweit, daß die Deckung auf eine eng begrenzte Zahl von Gefahren beschränkt ist. Aber das heißt nicht notwendigerweise, daß der Staat unter allen Umständen von der Intervention in den Märkten für Ertragsausfallversicherungen absehen sollte. Unter bestimmten Bedingungen können Pflichtversicherung und Subventionen zu einem Zuwachs an sozialer Wohlfahrt führen. Die Konklusion für Rußland besteht darin, daß die gegenwärtige subventionierte Allgefahren-Ertragsausfallversicherung abgeschafft und durch eine Spezielle-Gefahren-Versicherung ersetzt werden sollte, die nur eine begrenzte Zahl von Gefahren abdeckt. Ein mögliches Beispiel wäre eine Versicherung gegen das Risiko von Ernteverlusten durch den heißtrockenen Steppenwind Suchovej. Das Ob und Wie staatlicher Eingriffe in die Ertragsausfallversicherung sollte pragmatisch und in Abhängigkeit vom konkreten Fall gesehen werden.
urn:nbn:de:gbv:3:2-22851
Keywords: 330; Landwirtschaftliche Versicherung; Reorganisation; Vergleich; Russland; Tschechische Republik